Pengaruh Seleksi Karyawan Terhadap Produktivitas Kerja Pada PT. Aloma Wangi Bogor - Yuli Anwar; Erna Herpiana (Jurnal Ilmiah Binaniaga, 2008)
prospective workes who apply to companies not limited to comporate environments, but were outside the area even more numerous, better take a long time employee and for the information in the media for many companies the number of applicants, have a positive impact for workers who meet the qualifications and expectations. More and applicants, the more chances to choose a highly qualified workforce and competent. Conversely the negative impact the allocations of funds, time and energy to do the sekection of applicants who have spent quaite big. Employee productivity also related to the right of labor to obtain the potential development opportunities that exist in self-employees in accordance with the capabilities(education) and experience in order to increase its productivity. With the development of human resources through training, promotion and transfer of employees it is expected that employee productivity is achieved. Thereby increasing employee productivity is closely  related to human resource development issues, obtained regression equation Y = 0,889 + 0.002 X, meaning that if there is an increase of one unit of selection of employees so that productivity will increase employee’s 0,002. Obatained by calculating r (0.627)> r on the table for a = 0,05 (0.3340 then accept H1, which means there is a relationship to the level of employee selection employee producivity with the interpretation of the correlation coefficient indicates the interval betwwen 0.60 to 0.799 whitch has a positive relationship is strong.